Tributação ambiental sob o prisma dos princípios da proporcionalidade e da subsidiariedade - Araripe, Aline Bona de Alencar (2018)
The environmental crisis is shown through phenomena such as global warming, acid rain, the disappearance of some species of fauna and flora, the increase of air pollution index, among others. To protect the environment, it is necessary to develop public policies of environmental protection. In this context, environmental taxation is shown as a way to be followed, in search of influencing behaviors, through the use of extrafiscality, making people adopt sustainable postures. However, every taxation means an public interference in the individual right’s sphere, that were historically conquered and are essential to human dignity. In this work, it is intended to verify if the principles of proportionality and subsidiarity help the environmental taxation to complete its role as a tool of behavior modification, avoiding State’s abusive interventions. It is presupposed that the principles of proportionality and subsidiarity offer the harmonization needed between individual rights and state’s intervention, in order to protect the environment through the institution of taxes. This research is justified by the necessity of discussion about solutions for the environmental crisis. It is foreseen that the environmental taxation may be used as a fair and equitable way of promotion the environment’s defense. Therefore, the right to a healthy environment can be assured for the population as a whole, as well as to the generations yet to come. The research method used was bibliographic survey and national and international legislation analysis. The methodology was based on Edgar Morin’s complex thinking, which admits the end of the duality between subject and object. Thus, the research is influenced by the political, social, ideological and historical vision of the researcher. Therefore, it is understood that science is not essentially impartial, given that produced by human beings, and that every discovery is under the influence of the historical context and the discoverer’s personal inclinations.